Komposisi Komunitas Plankton dan Kualitas air di Gili Ketapang, Kabupaten Probolinggo, Jawa Timur - Agita Dwi Rosmalia Putri; Aida Sartimbul; Ating Yuniarti (Postgraduate, University of Mataram, 2023)
Gili Ketapang is an area with quite high fisheries potential, reaching 40% of the resource production in East Java. The catch season is often associated with the presence of plankton as the main source of food availability in marine ecosystems, influenced by season, weather, temperature, and water quality. The aim of this research is to report water quality results and analysis of phytoplankton and zooplankton composition in the coastal waters of Gili Ketapang, East Java. The method used in this research is quantitative descriptive to describe plankton composition and water quality in Gili Ketapang, East Java. In this study, 26 phytoplankton genera and 35 zooplankton genera were found. The abundance of phytoplankton and zooplankton measured in the West Season was lower compared to the abundance in Transition Season I. The phytoplankton and zooplankton diversity index showed moderate diversity (1<H'<3). In general, the results of water quality measurements obtained in the West Season were temperature 32.8 , pH 8.54, dissolved oxygen 6.72 mg/L, salinity 32.66 ppt, Secchi depth 13.11 m, and nitrate 1.39 mg/L. Meanwhile, the water quality in Transition Season I was respectively temperature 30.26 , pH 7.8, dissolved oxygen 8.24 mg/L, salinity 31.47 ppt, Secchi depth 10.92 m, and nitrate 1.21 mg/L.